A comparison of raw soybeans and soybean oil as energy sources for finishing pigs - Robert D Goodband; Robert H Hines; R C Thaler (Kansas Agricultural Experiment Station Research Reports, 1987)
Two hundred and seventy pigs averaging 125 lbs were utilized in two growth trials to determine the effects of raw soybeans or soybean oil on finishing pig performance. In each trial, raw soybeans or soybean oil were substituted for milo to provide 2 or 3% added fat. Pigs fed these diets were compared to pigs fed a milo-soybean meal diet (control). In Experiment 1, raw soybeans or soybean oil were added in place of milo in a 15% crude protein, .7% lysine diet. Increasing levels of raw soybeans resulted in greater trypsin inhibitor content compared to the control or soybean oil diets. Pigs fed diets containing soybean oil showed a slight tendency (P(.15) for improved average daily gain (ADG) compared to pigs fed raw soybeans. Pigs fed raw soybeans also had poorer feed efficiency (F/G) compared to those fed soybean oil (P<.0l) and the control diet (P<.05). Plasma urea concentrations measured on day 21 of the trial were lower for pigs fed the soybean oil diets than for pigs fed the control (P<.10) and raw soybean (P>.0l) diets. In Experiment 2, control pigs were fed a low protein, lysine-fortified diet (11.2% crude protein, .60% lysine). Pigs fed the control diet tended to have higher ADG (P<.12) and average daily feed intake (ADFI) than pigs fed diets containing raw soybeans or ,soybean oil. Feed efficiency was not influenced by dietary treatment. Plasma urea concentrations were highest (P<.0l) for pigs fed diets containing raw soybeans. These results indicate that, in a typical finishing diet (l5% crude protein, .7% lysine), the addition of raw soybeans as an energy source reduced pig performance compared to diets containing 2 or 3% soybean oil. Additions of raw soybeans also resulted in poorer F/G for pigs compared to the diet without added fat. However, when low protein diets were fed, fat additions from either soybean oil or raw soybeans resulted in slightly poorer pig performance compared to the control diet.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Raw soybeans; Soybean oil; Energy